2021
DOI: 10.1159/000515180
|View full text |Cite
|
Sign up to set email alerts
|

Low-Blood Lymphocyte Number and Lymphocyte Decline as Key Factors in COPD Outcomes: A Longitudinal Cohort Study

Abstract: <b><i>Background:</i></b> Smokers with and without chronic obstructive pulmonary disease (COPD) are at risk of severe outcomes like exacerbations, cancer, respiratory failure, and decreased survival. The mechanisms for these outcomes are unclear; however, there is evidence that blood lymphocytes (BL) number might play a role. <b><i>Objective:</i></b> The objective of this study is to investigate the relationship between BL and their possible decline over time wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Further, our study found levels of LYM to be lower among smokers than non-smokers. This finding is also in line with a study by Semenzato U. et al (2021) (32), who investigated the relationship between blood lymphocyte and its possible decline over time with long-term outcomes in smokers with and without chronic obstructive pulmonary disease. The study found the lymphocyte count to be lower in these patients (1,880 cells/µL) and a decline in the count to be related to the worst outcome among smokers with or without the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Further, our study found levels of LYM to be lower among smokers than non-smokers. This finding is also in line with a study by Semenzato U. et al (2021) (32), who investigated the relationship between blood lymphocyte and its possible decline over time with long-term outcomes in smokers with and without chronic obstructive pulmonary disease. The study found the lymphocyte count to be lower in these patients (1,880 cells/µL) and a decline in the count to be related to the worst outcome among smokers with or without the disease.…”
Section: Discussionsupporting
confidence: 92%
“…All subjects underwent a comprehensive clinical and functional examination including spirometry, maximum mid-expiratory flow at 25–75% of FVC (MMEF), measurement of diffusing capacity of the lung for carbon monoxide ( D LCO ), using the Communauté Européenne du Charbon et de l'Acier (CECA) as predicted values [ 13 ]. The 6-min walk test (6MWT), modified Medical Research Council (mMRC) Dyspnoea Scale and COPD Assessment Test (CAT) [ 14 ] were also obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Of interest, we have shown that the prevalence of lung cancer in smokers is inversely related to the severity of COPD, thus greater prevalence in the least severe disease ( 47 ). It could be hypothesized, based on our results, that the suppression of SOCS3 in smokers with mild and/or no COPD might play a role in the development of cancer in this population ( 48 ).…”
Section: Discussionmentioning
confidence: 83%